The Reverberations of the Covid-19-Hit International Diamond Market on Botswana - Kalo Makaloba (The Thinker)
A semi-desert country in southern Africa, Botswana has historically never had any economic significance – a narrative supported by how the country became a British protectorate in 1885, as opposed to the normal trend at the time of being forced into becoming a colony.